Indifference of Jakarta KRL Users: A Postive and Islamic Law Perspective - Adhkar, Shohibul (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2024)
This research examines the indifferent behavior of users of priority seats on the Electric Commuter Train in Jakarta. This deviant behavior occurs during the commuting hours, both in the morning and evening. This research was examined using qualitative research methodology and a case study approach. In this study, it was found that KRL passengers choose to ride the KRL so they can sit and rest during the journey on the KRL. The irony is that on every seat occupied in the KRL, there is an appeal to give up their seat for those who are classified as priority. Meanwhile, those who have already gotten a seat choose to be indifferent, either by sleeping or covering their ears with headphones while watching their phones or playing games during the journey. With that behavior, they hope not to have to bother giving up their seats to priority users during the journey. Our analysis of that behavior concluded that it is not in line with the ethical system that applies in the KRL. This occurs due to the low legal awareness of KRL users regarding the applicable norms. Likewise, the background of religious, social, and moral education plays an important role in the existence of such indifferent behavior. The existence of such indifferent behavior falls into the category of a modern humanitarian problem that is highly capitalistic. Degrading the value of humans in Islam as khalifatullah, because they are unable to make Allah the primary object of worship in every activity, especially by giving priority to those who are more deserving.